Current scenario, future possibilities and applicability of telemedicine in hilly and remote areas in India: A review protocol - Kaeley, Nidhi (J Family Med Prim Care, 2021)
In India telemedicine is ideal because of its diverse landmass, difficult terrain and huge population. India, a developing country is witnessing an increase in economic growth but growing health expenditure is still posing a challenge. Telemedicine offers a solution to bridge the gap between resources available and growing needs in the health care set up. It offers an opportunity for effective collaboration of primary and secondary health care setups and to reach population staying in underserved areas. The purpose of this article is to discuss current scenario, future possibilities and applicability of telemedicine in hilly and remote areas in India.